Ownership Type and Political Risk Transmission: Evidence from Indonesian Equity Markets - Priscilia Limadinata; William Santoso; Hermeindito Hermeindito (AIBPM Publisher, 2026)
Political shocks can be transmitted asymmetrically across firms, depending on their ownership structure, while aggregate indices, such as the Jakarta Composite Index (JCI), may mask divergent firm-level reactions. This study examines whether ownership type (State-Owned Enterprises (SOEs) versus private firms) moderates political risk transmission to stock returns and conditional volatility in the Indonesian equity market. Employing a quantitative event study with GARCH (1,1) volatility modeling, this study analyzes 46 firms across four political shocks in 2025 using a 2 x 2 framework (domestic vs. international shocks x ownership type). Results show that domestic political shocks generated significant positive CAR for SOEs (mean = 4.67%, t = 1.893, p = 0.036), consistent with mean-reversion. For international shocks, a significant episode x ownership interaction emerged (F = 16.425, p 0.001, ?² = 0.157), while the ownership main effect on CAR was not significant at the 5% level (p = 0.054). Although international ???? values were positive, the between-group difference was insignificant (p = 0.922), and the overall volatility model showed no ownership, shock-type, or interaction effects (F = 0.222, p = 0.881). These findings suggest that political risk in Indonesia is transmitted primarily through return direction rather than ownership-specific volatility amplification.